Design Thinking, Collaborative Innovation, and Neoliberal Disappointment: Cruel Optimism in the History and Future of Higher Education - Catterall, Kate; Mickenberg, Julia; Reddick, Richard (Radical Teacher, 2019)
The extensive amount of academic labor of minoritized faculty, especially at research institutions, has been well documented in the academic literature. Three tenured associate professors at The University of Texas present the genesis, evolution, and postscript of leading and serving in an initiative to de-silo and encourage collaboration across the university, culminating in a collaboratively taught course. Integrating concepts of teaching in the neoliberal university context, the gendered and raced distribution of academic labor, and slow scholarship, the authors discuss the pedagogically productive process of collective teaching and decision-making, the frustrations inherent when employing radical pedagogy, and institutional shifts that prioritize a customer-service model of teaching, learning, and rapid research productivity. The authors conclude with reflections and recommendations for scholar-researchers similarly placed in institutional contexts where encroachments upon academic freedom and an embrace of business models collide with personal goals of career satisfaction, collective work, and improving pedagogy.